Trading Off Generations: Infinitely-Lived Agent Versus OLG - Maik T. Schneider; Christian Traeger; Ralph Winkler (ETH Zurich, CER-ETH - Center of Economic Research, 2010)
The prevailing literature discusses intergenerational trade-offs predominantly in infinitely-lived agent models despite the finite lifetime of individuals. We discuss these trade-offs in a continuous time OLG framework and relate the results to the infinitely-lived agent setting. We identify three shortcomings of the latter: First, underlying normative assumptions about social preferences cannot be deduced unambiguously. Second, the distribution among generations living at the same time cannot be captured. Third, the optimal solution may not be implementable in overlapping generations market economies. Regarding the recent debate on climate change, we conclude that it is indispensable to explicitly consider the generations' life cycles.
Keywords: D63; H23; Q54; 330; climate change; discounting; infinitely-lived agents; intergenerational equity; overlapping generations; time preference; Klimawandel; Generationengerechtigkeit; Intertemporale Entscheidung; Overlapping Generations; Theorie